1996
DOI: 10.1113/jphysiol.1996.sp021366
|View full text |Cite
|
Sign up to set email alerts
|

Slow inactivation of Na+ current and slow cumulative spike adaptation in mouse and guinea‐pig neocortical neurones in slices.

Abstract: 1. Spike adaptation of neocortical pyramidal neurones was studied with sharp electrode recordings in slices of guinea-pig parietal cortex and whole-cell patch recordings of mouse somatosensory cortex. Repetitive intracellular stimulation with 1 s depolarizing pulses delivered at intervals of <5 s caused slow, cumulative adaptation of spike firing, which was not associated with a change in resting conductance, and which persisted when Co2+ replaced Ca2P in the bathing medium.2. Development of slow cumulative ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
281
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(307 citation statements)
references
References 40 publications
23
281
0
3
Order By: Relevance
“…Despite evidence that neurons possess a considerable reserve of Na v channels (Madeja, 2000), reductions in Na v channel availability during repetitive firing or pharmacological manipulation influence AP generation (Fleidervish et al, 1996;Colbert et al, 1997;Jung et al, 1997;Madeja, 2000;Colbert and Pan, 2002;Carr et al, 2003). In support of this principle, a 47% reduction in Na v channel availability in STN neurons with 5 nM TTX did not abolish pacemaking but did reduce its frequency and depolarized APth.…”
Section: Discussionmentioning
confidence: 70%
“…Despite evidence that neurons possess a considerable reserve of Na v channels (Madeja, 2000), reductions in Na v channel availability during repetitive firing or pharmacological manipulation influence AP generation (Fleidervish et al, 1996;Colbert et al, 1997;Jung et al, 1997;Madeja, 2000;Colbert and Pan, 2002;Carr et al, 2003). In support of this principle, a 47% reduction in Na v channel availability in STN neurons with 5 nM TTX did not abolish pacemaking but did reduce its frequency and depolarized APth.…”
Section: Discussionmentioning
confidence: 70%
“…Although the focus continued to be on AHP conductance summation, subsequent investigators considered other processes, particularly in studies on brainstem motoneurons, where the AHP conductance was found to contribute to the early but not later phases of SFA (Sawczuk et al, 1997;Powers et al, 1999;Viana et al, 1993). Studies in neurons of the substantia gelatinosa (Melnick et al, 2004), dorsal root ganglion cells (Blair and Bean, 2003), neocortical neurons (Fleidervish et al, 1996), and hypoglossal motoneurons (Powers et al, 1999) demonstrated that SFA was not necessarily dependent on the AHP and led to the suggestion that the slow inactivation of sodium currents may be a contributing factor.…”
Section: Spike Frequency Adaptationmentioning
confidence: 99%
“…Indeed, spike-frequency adaptation introduced by an AHP conductance does not cause noise to increase gain in leaky integrate-and-fire models (Rauch et al, 2003;La Camera et al, 2004), indicating that the ability of the sAHP to promote gain increases by noise must depend on interaction with other mechanisms. In neocortical pyramidal neurons, slow inactivation of voltage-gated Na ϩ channels contributes to spike-frequency adaptation and limits the maximal steady-state firing rate during strong stimuli (Fleidervish et al, 1996). Because of its shunting effect, the sAHP conductance may increase the Na ϩ conductance required to initiate a spike, enhancing the effect of Na ϩ inactivation and limiting the maximal firing rate.…”
Section: Relationship Between Noise Effects and Individual Action Potmentioning
confidence: 99%